Food safety knowledge, attitude and practices of food handlers in foodservice establishment at tourism attractions in Terengganu / Norzaidah Ngali, Norazlina Rahmat & Noralisa Ismail - Ngali, Norzaidah; Rahmat, Norazlina; Ismail, Noralisa (2013)
In Malaysia, issues on food safety are not new. More often than not, issues of unsafe food handling, doubtful food preparation, unsystematic food storage, HALAL issue and food poisoning have long been the concerns of the Malaysian public. Research by Howes et al (1996), Powell, Atwell and Massey (1997) and Clayton et al (2002) indicated that although training might increase the knowledge on food safety, this did not always result in positive changes in food handling practices. In relation to that, the failure of food handler to provide positive gastronomic experience such as good food handling during vacation will disrupt trips and tarnish destination reputations (Pendergast, 2006). This situation will also lead to tourists developing negative perception towards the eatery at tourism attractions.